Implementasi Teknologi Progressive Web App (PWA) Pada Sistem Informasi Kos-Kosan - Dwiyanto, Nova; Paputungan, Irving Vitra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
A boarding house is a residential service that offers rooms with flexible rental payments. However, transactions in most boarding houses are still conducted manually, where tenants have to send proof of payment to the owner and confirm that they have paid. This makes it difficult for tenants to ensure that their payments are received, and the owners also need to match the payment proofs with the recorded transactions. This situation is inefficient and can lead to administrative complexity as well as the risk of record-keeping errors. Therefore, a boarding house management information system is needed to simplify this process. The global mobile market share has risen from 0.67% in January 2009 to 47.96% in February 2019. This drives the need for mobile applications and responsive websites for mobile devices. However, developing mobile applications incurs higher costs compared to web-based system development. This article aims to create a boarding house management system using Progressive Web App (PWA) technology, which can simplify the payment and financial record-keeping processes, and can be installed like a native application, but with an easier installation process. The developed system successfully automates digital payments without manual verification, generates automatic bills, and sends notifications to tenants. The PWA implementation enhances the user experience by providing quick and easy access across various devices. As a result, the boarding house payment and transaction recording processes become more efficient, and user satisfaction is improved through a web application that delivers a mobile app-like experience.